Pengembangan Soal Serupa Pisa(Programme For International Student Assessment) Pada Konten Space And Shape Untuk Mengukur Kemampuan Penalaran Matematis Siswa Kelas IX SMP N 1 Jatiroto - Pangestika, Wahyu Widia, Prof. Dr. Budi Murtiyasa, M.Kom (2016)
Indonesia 's involvement in the Program for International Student Assessment ( PISA ) is one of the efforts to see the extent to which the success of the education program Indonesia compared with other countries in the world. This research was purposed to produce a valid and practical questions of PISA in Space and Shape content. The method used in this research was a research and development method. This research required two phases, namely preliminary and formative evaluation phases which includes self evaluation, expert reviews, one-to-one, small group and field test. Data collection techniques used by walkthrough, document, test, and interview. After going through one-to-one phase, small group, and field validation with descriptive matter in tested right at the stage of field test phase in class IX SMP N 1 Jatiroto. The test result overall with an average value of mathematical reasoning abilities 63,11, can be categorized into good mathematics reasoning ability, although there are still students who enter the category enough mathematical reasoning ability. However, these result can also be said that the development of similar PISA question categorized into valid and practical criteria and also has a potential effects on student's reasoning abilities. Keyword:reasoning ability, PISA, mathematics question, space and shape.